COLLAPSE BRECCIAS – A "NEW" TYPE OF ANTHROPOGENIC GEOLOGICAL FORMATIONS/BODIES/DEPOSITS IN THE KRYVYI RIH IRON ORE BASIN - POKALYUK, Volodymyr; VERKHOVTSEV, Valentyn; HUBINA, Victoria; YATSENKO, Viktor; ZABOROVSKA, Larisa; LAVRYNENKO, Olena; MAIBORODA, Evgen (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
On the basis of geological mapping, structural, mineralogical, petrographic, geochemical, petrophysical studies in the Pivdennyi and Pivnichnyi iron ore quarries of the Saksahansk district of the Kryvyi Rih iron ore basin (Kryvbas), a "new" morphological and genetic type of anthropogenic formations – collapse breccias formed as a result of rock masses displacement over underground mining zones – has been identified. These breccias make up huge volumes within the quarries, forming virtually new large-scale anthropogenic geological bodies with morphology, material composition and physical properties that differ from the original parent rocks. They occupy almost 100 % of the axial areas of the quarries, as well as significant volumes of their western ("hanging") sides. Together with the remnants of ferruginous quartzite and rich ore leftover from underground mining, they are the subject of modern industrial mining. Breccia collapses are new anthropogenic geological rocks. Genetically and morphologically, they fully correspond to the essence of anthropogenic formations and it is quite legitimate to apply the conceptual and legal framework of anthropogenic deposits to them in case of their economically feasible extraction, just as it is generally recognised for bulk dumps and sludge dumps. All this raises the question of the relevance of including these formations in the modern classifications of anthropogenic deposits of Kryvbas as a separate type.